Etymologic Features and Peculiarities of the Process of Indigenous Vocabulary Borrowing in American English - Domnich, Olga V. V. (Respectus Philologicus, 2016)
In this study, certain problems of taxonomy and etymology associated with the borrowings from indigenous languages into American English have been solved. The vocabulary of Amerindian and Eskimo-Aleut languages of the indigenous ethnic groups of North, South, and Central America in American English are the research material. After analyzing the etymological sources of autochthonous lexical units in AmE, it has been found that the process of borrowing lasted for five centuries (16–20 centuries). Despite this fact, the most part of the vocabulary has been lost in the absence of nomination objects, substituted by English synonyms or moved into the category of archaisms and historicisms and has not kept its relevance to the English-speaking usage. However, the author of this article has analyzed native lexical units, which are an integral part of the lexical system of modern American English; this fact is confirmed by the necessary introduction of the given lexical items into the register of authoritative lexicographical sources: references, explanatory dictionaries, and special dictionaries describing the lexical structure of modern AmE.